2014
DOI: 10.1016/j.celrep.2014.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomic Analysis of Human Mitochondrial RNA Processing

Abstract: Summary Both strands of human mitochondrial DNA (mtDNA) are transcribed in continuous, multi-genic units that are cleaved into the mature rRNAs, tRNAs, and mRNAs required for respiratory chain biogenesis. We sought to systematically identify nuclear-encoded proteins that contribute to processing of mitochondrial RNAs (mt-RNAs) within the organelle. First, we devised and validated a multiplex “MitoString” assay that quantitates 27 mature and precursor mtDNA transcripts. Second, we applied MitoString profiling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
1
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 52 publications
(92 reference statements)
8
116
1
11
Order By: Relevance
“…FASTK, the founding member, was described as an anti-apoptotic protein that shuttles between mitochondria and the nucleus (Simarro et al, 2010a). Silencing FASTKD3 produced a marked but yet-unexplained defect in respiration (Simarro et al, 2010b), and similar experiments on FASTKD4 showed changes in the stability of some mitochondrial mRNAs (Wolf and Mootha, 2014). Mutations in FASTKD2 were found in a patient with mitochondrial encephalopathy associated with an isolated complex IV deficiency (Ghezzi et al, 2008), but our data suggest a more pervasive combined OXPHOS assembly defect associated with loss of FASTKD2 function.…”
Section: Discussionmentioning
confidence: 88%
“…FASTK, the founding member, was described as an anti-apoptotic protein that shuttles between mitochondria and the nucleus (Simarro et al, 2010a). Silencing FASTKD3 produced a marked but yet-unexplained defect in respiration (Simarro et al, 2010b), and similar experiments on FASTKD4 showed changes in the stability of some mitochondrial mRNAs (Wolf and Mootha, 2014). Mutations in FASTKD2 were found in a patient with mitochondrial encephalopathy associated with an isolated complex IV deficiency (Ghezzi et al, 2008), but our data suggest a more pervasive combined OXPHOS assembly defect associated with loss of FASTKD2 function.…”
Section: Discussionmentioning
confidence: 88%
“…Despite early evidence that FASTK family proteins localize to mitochondria and, as demonstrated for FASTKD3, affect cellular respiration (Simarro et al 2010), mechanistic and functional information is only now beginning to emerge. A recent high-throughput screen for factors involved in mitochondrial RNA processing implicated FASTKD4 in the regulation of the turnover of a select spectrum of mitochondrial transcripts (Wolf and Mootha 2014). With the aim to identify the molecular underpinnings of a rare form of encephalomyopathy associated with mutated FASTKD2 (Ghezzi et al 2008), we here propose a mechanistic model for its function.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of mitochondrial gene expression is exerted post-transcriptionally as the steady-state levels of transcripts derived from common polycistronic precursors vary extensively in their abundance (Piechota et al 2006;Nagao et al 2008). Approximately 1400 nuclear genes are essential for multiple aspects of mitochondrial homeostasis including, among others, assembly of the ETC and mitochondrial transcript processing (Calvo et al 2006;Pagliarini et al 2008;Wolf and Mootha 2014). The identification of proteins binding polyadenylated transcripts in human cells by interactome capture revealed that many proteins lacking classical RNA-binding domains associate with RNA in human and mouse cells (Baltz et al 2012;Castello et al 2012;Kwon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…FASTKD1 belongs to a family of six metazoan-specific proteins containing both FASTK (Fas-activated serine/threonine kinase-like) and RAP (~60-residue RNA binding domain abundant in Apicomplexans) domains. While the functions of the five other FASTK family members have been studied by knockdown (Antonicka and Shoubridge, 2015; Jourdain et al, 2015; Simarro et al, 2010; Wolf and Mootha, 2014), FASTKD1 has not previously been examined.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is unique and without precedent that FASTKD1 is a specific negative regulator of ND3 mRNA. FASTK, FASKD2, FASTKD4, and FASTKD5, for example, are all positive regulators of specific mitochondrial mRNAs (Antonicka and Shoubridge, 2015; Jourdain et al, 2015; Simarro et al, 2010; Wolf and Mootha, 2014). Complex I is the least abundant complex of the electron transport chain (Schagger and Pfeiffer, 2001).…”
Section: Resultsmentioning
confidence: 99%